2014
DOI: 10.4081/ijas.2014.3285
|View full text |Cite
|
Sign up to set email alerts
|

A Survey on Feedlot Performance of Purebred and Crossbred European Young Bulls and Heifers Managed Under Intensive Conditions in Veneto, Northeast Italy

Abstract: This study, based on a nearly 10-year collection of performance data of young bulls and beef heifers, aimed to benchmark production traits of specialized fattening herds of northern Italy and to compare the performance of stock calves belonging to several European genetic types (GT). Data originated from 2806 batches (a group of stock calves homogeneous for GT, origin, finishing herd, fattening period, and diets), and concerned 188,891 animals of 10 GT herded in 44 farms of the Veneto region. For each batch, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
29
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 29 publications
6
29
0
Order By: Relevance
“…This is the case of the beef fattening system in the north-eastern Italy, which gives a notable contribution to the European beef supply (European Commission 2011). This system integrates the extensive suckler cow-calf farms of the French Massif Central, which provide stock calves, with the intensive beef herds of northern Italy, where imported stock calves are finished using total mixed rations based on maize silage and concentrates (Cozzi 2007;Gallo et al 2014). In a previous research published by our group, aiming to assess the environmental impact of this beef system (Berton et al 2016), we found a notable variation in different impact categories.…”
Section: Introductionmentioning
confidence: 99%
“…This is the case of the beef fattening system in the north-eastern Italy, which gives a notable contribution to the European beef supply (European Commission 2011). This system integrates the extensive suckler cow-calf farms of the French Massif Central, which provide stock calves, with the intensive beef herds of northern Italy, where imported stock calves are finished using total mixed rations based on maize silage and concentrates (Cozzi 2007;Gallo et al 2014). In a previous research published by our group, aiming to assess the environmental impact of this beef system (Berton et al 2016), we found a notable variation in different impact categories.…”
Section: Introductionmentioning
confidence: 99%
“…soybean meal as a co-product of soybean oil production), an economic allocation method was used, since this is the most common method in livestock sector (de Vries and de Boer, 2010). Within these boundaries, the reference unit was the batch, defined as a group of animals homogeneous for genotype, sex, origin, fattening farm and finishing period (Gallo et al, 2014). This approach allowed to take into account the variation of the impact among and within farms.…”
Section: Origin Of the Data Goal And Scope Definitionmentioning
confidence: 99%
“…The study considered 327 batches (20,598 animals, 63 732 heads of average size) herded in 16 beef fattening farms whose geographical location, ownership type, and herd structure and management were typical of this specialized beef sector (Gallo et al, 2014). The reference year was 2013.…”
Section: Origin Of the Data Goal And Scope Definitionmentioning
confidence: 99%
See 1 more Smart Citation
“…Charolais purebred animals are mainly born and raised in the mideastern and the western part of France (Bouquet, 2009). Crossbred calves are born in various regions in France and are mainly sold to fattening farms in the northeast region of Italy (Sarzeaud et al, 2007;Gallo et al, 2014). The mideastern and the western part of France have an oceanic climate and the northeast region of Italy has a Mediterranean climate.…”
Section: Genetic Differences At the Trait Levelmentioning
confidence: 99%